The role of philosophy of mathematics education in mathematics teacher education - Samuel Kwaku Boadu; Ebenezer Bonyah (Cogent Education)
This study aims to examine the impact of integrating the role of philosophy of mathematics education in mathematics teacher education on student learning outcomes and attitudes towards mathematics. Purposive sampling technique was used to recruit 10 in-service mathematics teachers from a Technical School in Kumasi. A qualitative case study approach was adopted to gather data from mathematics teachers through structured interviews. The data analysis technique employed in the study was reflexive thematic analysis. The study highlighted that the integration of philosophy of mathematics education enhances teachers' knowledge leading to a shift in instructional practices towards more inquiry-based and student-centered approaches. Students exposed to the philosophy of mathematics education in their mathematics classrooms demonstrated improved learning outcomes, enhanced critical thinking skills and deeper conceptual understanding of mathematical concepts. Also, students' attitudes towards mathematics were positively influenced. Notwithstanding the positive impact on students learning outcomes, there were challenges and barriers associated with integrating the philosophy of mathematics education into mathematics teacher education, including institutional constraints, teacher beliefs, time constraints, and limited resources. One significant contribution of this study is its demonstration of how integrating the philosophy of mathematics education into mathematics teacher education can fundamentally enhance both teaching practices and student learning outcomes.